2020
DOI: 10.35808/ijeba/463
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality and Foreign Direct Investment Inflows: Evidence from Cross-country Data with Policy Implication

Abstract: Purpose: The study examines the impact of institutional quality on Foreign Direct Investment (FDI) inflows for emerging economies from South Asiain the period 2002-2016. Other economic factors such as globalisation, financial development, and GDP are also considered. Design/Methodology/Approach: The study uses Im-Pesaran-Shin (IPS) panel unit root test to check stationarity property. It uses cross dependency (CD) and cross-sectional augments IPS tests to check cross-sectional dependency and heterogeneity acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Government effectiveness is showing a mixed result. Our results are in line with those of Gani (2007), Masron and Abdullah (2010), Buchanan et al (2012), Dang (2013) and Behera (2020).…”
Section: Resultssupporting
confidence: 93%
“…Government effectiveness is showing a mixed result. Our results are in line with those of Gani (2007), Masron and Abdullah (2010), Buchanan et al (2012), Dang (2013) and Behera (2020).…”
Section: Resultssupporting
confidence: 93%
“…This means that overall governance enhances the impact of FDI on economic growth. Behera et al (2020) found the existence of a long-run relationship between governance indicators and FDI inflows for South Asian countries.…”
Section: Review Of Literaturementioning
confidence: 97%
“…The studies on governance environment as a pull factor that influences capital inflow are prevalent and the results seem conclusive and consistent with conventional wisdom that improvement in governance quality attracts capital inflow. For example, many studies found that governance quality affects aggregate capital flows (Alvarez, 2015;Biro, Erdey, Gall, & Markus, 2019;Khan, Khan, Jan, Jandan, & Khan, 2019;Wijethunga & Dayaratne, 2018;Wu, Li, & Selover, 2012); some provide evidence that governance quality attracts portfolio investment and FDI (Behera, Mishra, Priyadarshini, & Satpathy, 2020;Bouchoucha & Yahyaoui, 2019;Gok & Dogru, 2016;Layla et al, 2020;Sabir, Rafique, & Abbas, 2019;Yakubu, 2020). However, the studies that identify a set of essential individual governance indicators that attract capital flows are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Adegboye, Osabohien, Olokoyo, Matthew and Adediran (2020) revealed that institutional quality affected the FDI inflows in sub-Saharan Africa. In another cross-country paper for South Asia, Behera, Mishra, Priyadarshini and Satpathy (2020) showed that institutional quality led to FDI inflows when combined with either financial development or globalization. Jurčić, Franc and Barišić (2020) found that in Croatia, institutional quality variables such as control of corruption, political stability, regulatory quality, the rule of law and government effectiveness were not relevant in attracting FDI inflows.…”
Section: Empirical Reviewmentioning
confidence: 99%